OPTIMALISASI PROGRAM JAMINAN KESEHATAN NASIONAL DALAM RANGKA PENDAFTARAN PERALIHAN HAK ATAS TANAH BERDASARKAN DARI SURAT EDARAN MENTERI ATR BPN NO.5/SE-400.HK.02/II/2022 - Akhir, Muhammad Rhobiul; Fuad, Fokky; Rifai, Anis (Universitas Ekasakti, 2023)
The transition process in the process of buying and selling land requires the active participation of land buyers in the JKN-KIS program, so the buying and selling process will take quite a long time and seem complicated. The purpose of this study is to find out the legal consequences and obstacles encountered in implementing Circular Letter Number 5/SE-400.HK.02/II/2022 Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in transferring land rights. This study uses empirical research using two research approaches, namely Sociology of Law and Legislation. The results of this study indicate that the implementation of the implicit law of Circular Number 5/SE-400.HK.02/II/2022 Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in the transfer of land rights is a delay in the completion and ownership of documents. Certificates, lack of legal certainty, emergence of disputes between PPAT and BPN, violation of legal standards regarding the implementation of BPJS requirements and the effect of ineffective service processes and no relevant rights between BPJS ownership and registration of land ownership. . The obstacles faced were complaints from PPAT that not all customers were registered as active BPJS participants and there was an exception for land certificates of 25% because the buyer did not meet the requirements as an active BPJS participant.